A validation study of the clinical diagnosis of Dup15q syndrome: Which symptoms matter most?. (January 2020) - Beghi, E.; Giussani, G.; Bianchi, E.; Randazzo, G.; Sarcona, V.; Elia, M.; Striano, P.; Verrotti, A.; Ferretti, A.; Rebessi, E.; Specchio, N.; Bonanni, P.
Highlights: This is the first attempt to validate the diagnosis of Dup15q syndrome. Concordance among experts on the diagnosis is at best moderate. Feeding difficulties, hypotonia and epilepsy can be diagnostic markers. Abstract: Purpose: Dup15q syndrome is a rare genetic disease with a fairly nonspecific phenotype, clinical heterogeneity, and a wide spectrum of severity. However, no formal characterization has been attempted to select clusters of symptoms, signs and instrumental tests, to be used in the differential diagnosis with other neurodevelopmental disorders. Thus, our purpose was to identify symptoms, signs and instrumental findings, singly or in various combinations, favoring the early diagnosis of the Dup15q syndrome and the indication for genetic testing. Methods: 25 patients with Dup15q syndrome and 25 age and sex matched controls with other neurodevelopmental disorders were the study population. Patients' history, clinical and instrumental assessment were examined by five expert child neurologists blind to the genetic diagnosis. Each rater was asked to make the diagnosis in three subsequent steps: 1. Revision of the medical records; 2. Examination of the videorecorded clinical findings; 3. Assessment of the instrumental tests. Inter-rater agreement was measured with the Kendall's coefficient of concordance) and the Kappa statistic. Sensitivity, specificity and predictive values for symptoms, signs and instrumental findings, singly or in various combinations, were measured. Results: The Kendall's coefficient for the diagnosis of Dup15q syndrome was 0.43 at step 1 was 0.43, at step 2 was 0.42, at step 3. Patients with past feeding difficulties, hypotonia during the neonatal period, and epilepsy had >80 % probability of having the Dup15q syndrome. Conclusion: Feeding difficulties, hypotonia and epilepsy, though unspecific, can be used as signals of Dup15q syndrome and focused search of genetic abnormalities.